ANALISIS KEPERILAKUAN WAJIB PAJAK ORANG PRIBADI DALAM MENGGUNAKAN LAYANAN E-FILING PAJAK (Studi Pada Dosen Pegawai Negeri Sipil di Universitas Brawijaya Malang) - Zulkarnaen, Muhammad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
The use of e-filing in national level is popular among taxpayer, but it is still less favorable in the regional scale of East Java III. The objective of this research is to understand the behavioral acceptance of taxpayers toward e-filing through factors that affect its real usage based on the Theory of Reasoned Action (TRA), Technology Acceptance Model (TAM), and Theory of Planned Behavior (TPB). The respondents of this research are 70 civil servant lecturers of Brawijaya University who have used e-filing. The data of this study were collected through questionnaires and were analyzed using Partial Least Square (PLS) analysis in SmartPLS 3.2.7. The result shows that factors which positively influence behavioral acceptance of taxpayers toward e-filing are perceived usefulness, perceived ease of use, attitude toward use, interpersonal influence, external influence, subjective norm, and behavioral intention. In addition, most respondents agree that e-filing is acceptable for online tax reporting system. Keywords: Theory of reasoned action (TRA), Technology Acceptance Model (TAM), Theory of Planned Behavior (TPB), e-Filing, Actual Behavior.